Nutrient recovery from greywater treatment system at Unimas - Zuraida, Wael @ Mahzen (Universiti Malaysia Sarawak (UNIMAS), 2008)
The efficiency of two macrophytic plants that was water lettuce (Pistia stratiotes) and water hyacinth (Eichhornia crassipes), in removal of phosphorus and nitrogen from wastewater was being studied. Also the recovery of phosphorus and nitrogen through composting process was studied. The experiment was conducted using greywater that had been treated using the biofilter. The phosphorus and nitrogen content in the greywater and in both leaves and root system of the macrophytic plants were studied. The parameter that had been evaluated was dissolved oxygen, pH, temperature, nitrogen and phosphorus content. In term of the efficiency of the nutrient reduction of wastewater, the water lettuces' leaves had better performance compared to water hyacinth. Different story was for the roots system where the water hyacinth gave the best performance. For the recovery of the nutrient, the composting method was applied. However, the percentage of phosphorus and nitrogen content was low in the composted plant. In terms of the percentage of recovery of nitrogen in the composted plants, water lettuces' leaves (2.16%) had better recovery, followed by water lettuces' roots (1.67%), then water hyacinth roots (1.48%) and finally water hyacinth leaves (1.21 %). While for phosphorus, water lettuces' roots (0.44%) had better recovery followed by water lettuces' leaves (0.38%), then water hyacinths' roots (0.36%) and finally water hyacinths' leaves (0.22%) ..